2018
DOI: 10.1093/annonc/mdy049
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BLM promotes DNA damage and increased sensitivity to platinum salts in triple-negative breast and serous ovarian cancers

Abstract: BackgroundPlatinum-based therapy is an effective treatment for a subset of triple-negative breast cancer and ovarian cancer patients. In order to increase response rate and decrease unnecessary use, robust biomarkers that predict response to therapy are needed.Patients and methodsWe performed an integrated genomic approach combining differential analysis of gene expression and DNA copy number in sensitive compared with resistant triple-negative breast cancers in two independent neoadjuvant cisplatin-treated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
(18 reference statements)
1
42
0
Order By: Relevance
“…3C). In contrast, the expression of BLM, FEN1, and BRCA2 (direct transcriptional targets of BRCA1 that are negatively regulated) was upregulated in HRD tumors 21,22 , as was expression of EXO1, NEIL3, and BRIP 23 . The protein expression of FANC family members was also upregulated.…”
Section: Resultsmentioning
confidence: 97%
“…3C). In contrast, the expression of BLM, FEN1, and BRCA2 (direct transcriptional targets of BRCA1 that are negatively regulated) was upregulated in HRD tumors 21,22 , as was expression of EXO1, NEIL3, and BRIP 23 . The protein expression of FANC family members was also upregulated.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to the DDR pathway gene set, we analyzed tumor protein p53 (TP53), RB transcriptional corepressor 1 (RB1), ERCC excision repair 2, TFIIH core complex helicase subunit (ERCC2), BLM RecQ like helicase (BLM), and DNA topoisomerase I (TOP1) gene, which were previously reported to be related with platinum sensitivity. 2,9,[23][24][25][26][27] Tissue Preparation and Tumor Sequencing All tumor specimens were reviewed by pathologists to determine the percent of viable tumor and adequacy for sequencing. Genomic DNA was extracted from formalin-fixed paraffin-embedded tissue using a Qiagen DNA formalin-fixed paraffin-embedded tissue kit, and from fresh tissue using a QIAamp DNA mini kit (Qiagen, Redwood City, California).…”
Section: Genes and Gene Set Related To Ddr Pathway Selected For The Smentioning
confidence: 99%
“…Previous studies showed that overexpression of BLM displaces the localization of RAD51 to the sites of DNA damage 109 , 112 . The loss of RAD51 leads to insufficient HR resulting in genomic instability and DNA damage.…”
Section: Resultsmentioning
confidence: 94%
“…Biochemical studies showed that the deletion of BLM enhances the assembly of RAD51 at the ssDNA break site, while overexpression of BLM disrupts the RAD51 assembly through its helicase activity 108 , 109 . Therefore, BLM works as a ‘anti-recombinase’ at early and late stages of HR by: (i) preventing HR by disrupting the RAD51 assembly on the ssDNA of DSBs to make sure that HR only occurs between sequences with high homology; and (ii) preventing SCEs by separating the repaired DNA from the template DNA strand that arises at the final stages of HR 110 , 111 .…”
Section: Resultsmentioning
confidence: 99%